Ethic Leadership, Compensation for Work Engagement with Satisfaction as a Mediating Variable - Wahno Sahid; Ferryal Abadi (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2023)
In the progress of an organization it is necessary to have employee involvement so that the wheels of the company become more solid and stronger. For employees to be involved in work, very good supporting factors are also needed, such as ethical leadership, compensation and employee satisfaction. This study tries to examine the relationship of these variables by making satisfaction a mediating variable. This quantitative research was conducted using 170 respondents at a trading company in Jakarta using the Structural Equation Model (SEM) method. This study found that Compensation and Satisfaction have a positive effect on Work Engagement, Ethical Leadership does not have a positive effect on Work Engagement. Besides that, the indirect effect of satisfaction significantly mediates ethical leadership and compensation on Work Engagement. Suggestions for future researchers to develop this research by adding other variables that can affect work engagement.